Fabrication of heat sinks by Selective Laser Melting for convective heat transfer applications - Wong, Kin Keong (2021)
In this paper, the forced convective heat transfer performance of heat sinks produced by Selective Laser Melting (SLM) was experimentally investigated. Three heat sinks comprising pin fins of circular, rectangular-rounded and aerofoil geometries were fabricated by SLM from aluminium alloy AlSi10Mg powder. The heat sinks were tested in a rectangular air flow channel for convective heat transfer performance. Experiments performed for Reynolds numbers ranging from 3400 to 24,000 show that the heat transfer performances of the aerofoil and rectangular-rounded heat sinks exceeded those of the circular heat sink. Using the cylindrical heat sink as a benchmark, the average enhancements in the normalised Nusselt numbers were computed to be 15.0% and 21.4% for the rectangular-rounded and aerofoil heat sinks, respectively. It was demonstrated that SLM can be employed to design and fabricate heat sinks of customised geometries for heat sink applications.